2022
DOI: 10.1177/02601060221122153
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional knowledge and immunity-boosting food consumption patterns before and after the COVID-19 pandemic lockdown periods in Osun State, Nigeria

Abstract: Background: A healthy diet can ensure a robust immune system that can resist any onslaught by viruses and bacteria. Aim: To assess the nutritional knowledge and consumption patterns of immunity boosting foods of adults before & after the COVID-19 pandemic lockdown periods and the effect of the lockdown on daily food intake among respondents in selected towns in Osun state. Methods: Cross sectional data was collected from six largest local governments areas purposively selected from the three senatorial dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…As previous studies showed, an increase in the nutrition knowledge level is related to an increase in the consumption of essential food groups, such as grains, dairy, meats, beans, and so on ( 54 , 55 ). Especially during the COVID-19 pandemic, nutritional knowledge was significantly associated with the consumption of healthy foods to ensure a robust immune system ( 56 ). A healthy eating project in Poland suggested that increasing individuals’ nutrition knowledge was an important target to improve their lifestyles and dietary quality throughout the whole lifespan ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…As previous studies showed, an increase in the nutrition knowledge level is related to an increase in the consumption of essential food groups, such as grains, dairy, meats, beans, and so on ( 54 , 55 ). Especially during the COVID-19 pandemic, nutritional knowledge was significantly associated with the consumption of healthy foods to ensure a robust immune system ( 56 ). A healthy eating project in Poland suggested that increasing individuals’ nutrition knowledge was an important target to improve their lifestyles and dietary quality throughout the whole lifespan ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies suggest that the pandemic affected negatively food consumption patterns and diets, especially during the period of lockdown [48,53]. However, other studies posit that attention to health and healthy diets, especially those presumed to boost the immune system, increased during the pandemic [59,60,67,72]. Further studies deal with food (in)security during the pandemic [66,94,112].…”
Section: Agriculture Subsectors and Food Chain Stagesmentioning
confidence: 99%
“…This, as well as the reduction in physical activity/exercise especially during the lockdown [53], caused an increase in the prevalence of non-communicable diseases. However, there was, at the same time, an increase in attention to and interest in health [59,60,72]. For that, some scholars suggest that the pandemic improved nutritional knowledge [59,120].…”
Section: Impacts On Food Security and Nutritionmentioning
confidence: 99%
See 2 more Smart Citations